The Relationship Between Breakfast Habits and Learning Achievement in Student of Senior High School 1 Kertosono Nganjuk Regency - Paramita, Shafira Dyah; Nur Hatijah; Riezky Faisal Nugroho; Ergia Latifolia; Nyin , Ang Yeow (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Breakfast is an actual meal that is had between 6:00 and 9:00 in the morning and contribute provide 15 to 30 percent of the daily energy intake. Breakfast in the morning is very important for school children because it will have an impact on their learning achievement. This study aimed to examine the correlation between breakfast habits and learning achievement in students of SMA Negeri 1 Kertosono Nganjuk Regency. This study uses a cross-sectional design and is an analytical observational study. Simple random sampling was the sample method employed, with a sample size of 58 students. The data collection method was carried out by interviewing breakfast habits and taking data on the value of the 2nd Midterm Exam in the 2023/2024 academic year. The results of statistical tests utilizing the Spearman Rank Correlation test appear that there's no relationship between breakfast habits and learning achievement in students of SMA Negeri 1 Kertosono Nganjuk Regency. Nevertheless, students are expected to always have breakfast every day with a diverse menu and portions in accordance with balanced nutrition guidelines before carrying out learning activities at school.